Pengaruh Likuiditas, Leverage, Investment Opportunity Set, Dan Firm Size Terhadap Kualitas Laba - Hwang, Helvina; Viriany, Viriany (GEMA EKONOMI, 2023)
The aim of this study is to measure the effect of liquidity, leverage, investment opportunity set, and firm size on the earning quality of plastic and packaging industries that is listed on the Indonesia Stock Exchange in 2019-2022. There are 19 plastic and packaging companies in the population tested in this study and the non-probability sampling technique (purposive sampling) is taken in choosing the samples by applying several criterias. The sample data used in 48 data with a total of 12 companies. The data will be processed using SPSS ver.25. In this study, several tests are carried out such as classical assumption test and multiple linear regression. This research shows that Liquidity, Leverage and Investment Opportunity Set have no effect on Earnings Quality. On the other hand, Firm Size has a negative effect on Earnings Quality